2020
DOI: 10.1021/acsphotonics.0c00528
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Quantum Emitter in Aluminum Nitride

Abstract: A device that is able to produce single photons is a fundamental building block for a number of quantum technologies. Significant progress has been made in engineering quantum emission in the solid state, for instance, using semiconductor quantum dots as well as defect sites in bulk and two-dimensional materials. Here we report the discovery of a room-temperature quantum emitter embedded deep within the band gap of aluminum nitride. Using spectral, polarization, and photon-counting time-resolved measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 31 publications
4
46
1
Order By: Relevance
“…[20] In 2018, Zhou et al had reported near-infrared emitters based on GaN with high photon purity. [21] In 2020, Xue et al and Bishop et al had reported room-temperature single-photon emission in AlN, [22,23] the antisite-nitrogen-vacancy (N Al V N ) and divacancy (V Al V N ) were predicted to be possible sources of the single-photon signal. [22] As the III-nitrides belong to ionic semiconductor, the dangling bond energy level lies in the lower part of the bandgap for cation vacancy (V cation ), while it lies in the upper part of the bandgap for anion vacancy (V anion ).…”
Section: Introductionmentioning
confidence: 99%
“…[20] In 2018, Zhou et al had reported near-infrared emitters based on GaN with high photon purity. [21] In 2020, Xue et al and Bishop et al had reported room-temperature single-photon emission in AlN, [22,23] the antisite-nitrogen-vacancy (N Al V N ) and divacancy (V Al V N ) were predicted to be possible sources of the single-photon signal. [22] As the III-nitrides belong to ionic semiconductor, the dangling bond energy level lies in the lower part of the bandgap for cation vacancy (V cation ), while it lies in the upper part of the bandgap for anion vacancy (V anion ).…”
Section: Introductionmentioning
confidence: 99%
“…The wide‐field method can be directly implemented as long as the spatial PL or electroluminescence (EL) maps of quantum emitters can be well‐observed. To date, such EL and PL maps required for this positioning technique have been achieved with the colloidal QDs ( Figure a), [ 85 ] defect states in hexagonal boron nitride monolayers (Figure 7b) [ 86 ] and 2D tungsten‐diselenide (WSe2) monolayers (Figure 7c), [ 87 ] color centers in diamond (Figure 7d), [ 88 ] AlN (Figure 7e), [ 89 ] SiC (Figure 7f), [ 90,91 ] and cesium lead halide perovskite nanocrystals (Figure 7g) [ 92 ] at room temperature for the deterministic coupling to both plasmonic [ 93,94 ] and dielectric [ 95–98 ] photonic nanostructures. Together with techniques to locally and independently tune the emission wavelength of individual quantum emitters, as has been done for QDs using piezoelectric actuators, [ 99,100 ] it is likely feasible to pursue large‐scale deterministically‐coupled devices, [ 101 ] for example, strongly coupled systems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Equation ( 3) makes clear what affects the brightness of electrically driven single-photon sources based on color centers in semiconductors. The lifetime of most color centers is only of the order of a few nanoseconds, [27,29,[103][104][105] while the electron and hole capture processes are orders of magnitude slower. As discussed above, the hole density in diamond is of the order of 10 14 cm −3 , and the electron density is even lower.…”
Section: Single-photon Electroluminescence Ratementioning
confidence: 99%